Malnutrition and Cognitive Impairment Assessment of Elderly Tribal People of Bankura District, West Bengal by using MNA and MMSE Questionnaire - Joydeb Saha; Sk. Nazibar Rahaman; Saheli Ghosal; Subhash Kanti Roy; Jagannath Ghosh (The Bioscan, 2024)
Background: Mental problems and malnutrition are more common as people age. Both cognitive status and malnutrition are significantly influenced by sociodemographic factors. Because they lack many opportunities, tribal elders are the most vulnerable group in any type of healthcare facility. Method: A cross-sectional community study has been carried out in Bankura District, West Bengal. A total of 400 elderly tribal individuals were identified from four blocks using the stratified random sample procedure. The nutritional state and cognitive function of the elderly were measured using the Mini Nutritional Assessment (MNA) tool and the Mini Mental State Examination method (MMSE). Data has been uploaded into Microsoft Excel 2010 and analysed with SPSS version 20. Results: The results of MNA revealed that 26% and 49% of the elderly subjects were malnourished and at risk malnourished respectively. Sociodemographic factors like age related degeneration, low income, low education, nuclear family and socio-economic class are significantly responsible for malnutrition. It is also found that large malnourished are severe cognitive impairment. Conclusions: Malnutrition and cognitive impairment occurred frequently among the elderly tribal people in the study area. Malnutrition must be identified without delay and cognitive function tests need to be performed to maintain nutritional status to avert dementia.